Cohort-based programs facilitate skill development and community building for postdoctoral scholars: a pilot study - Nguyen, Karena H. (Frontiers in Education, 2024)
Postdoctoral scholars (“postdocs”) occupy a distinct academic stage and therefore have unique career and professional development needs. We aimed to explore whether a cohort-based program could promote skill development, support career preparation, and facilitate community building among postdocs at our institution. We applied the design thinking process, commonly used in engineering and industrial design, to create a 4-month long leadership and project management program. Pre- and post-surveys with Likert-scale questions measured participants' self-confidence in and self-assessment of competencies related to leadership and project management (e.g., creating an inclusive environment, developing a project charter). Fourteen postdocs from STEM and humanities disciplines participated in the pilot program. Matched responses from participants indicated an 82% positive shift in leadership self-confidence (n = 11) and a 56% positive shift in project management self-confidence (n = 9). Postdocs also showed a positive shift in all 12 competencies related to leadership (n = 11), and a positive shift in nine of 10 competencies related to project management (n = 9). In the optional open-ended questions provided in the surveys, postdocs articulated that the cohort created an environment to share experiences, safely practice new skills, and discuss their career goals. Applying the principles of design thinking to develop a cohort-based professional development program resulted in participant learning gains and their feedback suggests that the program supported a greater sense of belonging. Administrators could use our approach to innovate programming that meets the professional and personal needs of postdocs at their institution.